An iron-based stainless steel porous material and a method for producing the same
Patent Information
- Application Number
- CN202311644841.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-04
AI Technical Summary
[0004]为解决现有的金属多孔材料普遍存在的耐热性有限,耦合腐蚀情况下难以快速形成连续致密氧化膜,以及在遭受热冲击和机械冲击后使得反应过程中形成的氧化膜容易出现开裂、剥落等情况,导致金属多孔材料的高温抗氧化腐蚀性能不佳的问题,本发明提供了一种铁基不锈钢多孔材料,以及该多孔材料的制备方法
本发明通过在合金中添加铝元素以及一定含量的氧化物,实现了铁基不锈钢多孔材料及其表面钝化膜一体化制备,所制得的原位钝化膜复合的铁基不锈钢多孔材料具有广阔的应用前景,在高温过滤、催化剂载体等领域均可以得到广阔的应用;所制得的原位钝化膜复合的铁基不锈钢多孔材料所得的样品拥有良好、均匀的孔道结构、优异的耐高温腐蚀性能以及便捷的使用工序,具备更长的使用寿命。
Smart Images

Figure CN117900479B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloy materials, and particularly relates to an iron-based stainless steel porous material and its preparation method. Background Technology
[0002] Porous metallic materials possess excellent machinability, weldability, toughness, and superior heat and mass transfer properties. As key high-temperature filter media or catalyst supports, they demonstrate unique technological advantages and broad application prospects in numerous high-temperature chemical and clean energy production and conversion fields, such as crude oil catalytic cracking, biomass gas purification, and solid oxide fuel cells. Currently, porous metallic materials have replaced ceramic porous filter media and catalyst supports in some medium- and low-temperature operating conditions. However, stable service life of these materials in high-temperature conditions above 700℃ still faces significant challenges. Improving the high-temperature performance of porous metallic materials is a research hotspot and key application technology requirement in the fields of high-temperature filtration and high-temperature catalytic reactions both domestically and internationally.
[0003] However, during high-temperature service, the formation of high-temperature oxide films and corrosion processes in corrosive atmospheres often occur simultaneously in porous metallic materials. This not only limits the formation of continuous oxide films but also easily leads to excessive thickening of the oxide or corrosion films, affecting the pore structure stability of the porous metallic materials. Furthermore, under frequent thermal and mechanical shocks, the oxide films formed during the reaction process are prone to cracking and peeling. In particular, the high specific surface area of porous metallic materials accelerates the consumption of film-forming elements, and the porous framework with extremely small radii of curvature easily exacerbates oxide film detachment. When local oxide film protection fails, the highly exposed large-angle grain boundaries in the porous metallic materials become channels for the diffusion of oxygen (O), sulfur (S), and carbon (C) atoms into the alloy matrix, leading to grain boundary oxidation or intergranular corrosion, resulting in a continuous decline in mechanical properties. Traditional design approaches for porous materials used in high-temperature environments often improve the high-temperature protection performance of porous metallic materials by adding pre-oxidation processes to form pre-oxide films. However, pre-oxidation is not only difficult to control in terms of oxidation degree, but the additional high-temperature process also consumes more energy, increasing costs. The key to solving the problem lies in how to construct an in-situ passivation film during the material preparation process. This not only effectively simplifies the preparation process of pre-oxidized porous metal materials, but also ensures better adhesion between the in-situ passivation film and the substrate framework, and makes it easier to control the degree of oxidation. Summary of the Invention
[0004] To address the common problems of limited heat resistance, difficulty in rapidly forming a continuous and dense oxide film under coupled corrosion conditions, and the tendency of the oxide film formed during the reaction process to crack and peel off after thermal and mechanical shocks, resulting in poor high-temperature oxidation and corrosion resistance of porous metal materials, this invention provides an iron-based stainless steel porous material and a method for preparing the porous material.
[0005] The purpose of this invention is: 1. It can achieve the integrated in-situ formation of metal porous materials and their surface passivation films during the preparation of porous materials; Second, ensure that the obtained in-situ passivation film has good thermal stability; 3. Improve the bonding stability between the in-situ passivation film and the porous material matrix.
[0006] To achieve the above objectives, the present invention adopts the following technical solution.
[0007] A method for preparing iron-based stainless steel porous materials. The method includes: 1) Take iron-based stainless steel pre-alloy powder, aluminum powder and oxide powder and mix them evenly to obtain a mixed powder; 2) Press the mixed powder obtained in step 1) into a rough blank; 3) The blank obtained in step 2) is subjected to temperature-controlled sintering to obtain iron-based stainless steel porous material.
[0008] Preferably, the stainless steel pre-alloyed powder in step 1) contains 10-20 wt% Cr, 5-10 wt% Ni, and the balance is Fe and unavoidable impurities; Step 1) The oxide powder is a transition metal oxide powder.
[0009] As a preferred option The amount of aluminum powder used in step 1) is 5-10 wt% of the mass of the iron-based stainless steel pre-alloyed powder; The amount of oxide powder used in step 1) is 4 to 12 wt% of the mass of the iron-based stainless steel pre-alloyed powder.
[0010] As a preferred option The iron-based stainless steel pre-alloyed powder and aluminum powder mentioned in step 1) have a mesh size of 200-500 mesh; The oxide powder in step 1) has a particle size of 0.1 to 1.0 μm.
[0011] As a preferred option Step 2) Granulation treatment is performed on the mixed powder before pressing it into a rough blank; The granulation process involves mixing the powder and the forming agent until a paste is formed, drying it under a protective atmosphere or vacuum, and then sieving it to obtain a mixed powder with a mesh size of 30 to 100.
[0012] As a preferred option The molding agent is stearic acid and / or PVB and / or PVA and / or PEC; The molding agent is dissolved in a solvent and then mixed with the mixed powder. The mass ratio of the molding agent to the solvent is (0.05-0.20):1, and the solvent is ethanol and / or water. When the mixed powder is mixed with the molding agent, the mass ratio of the mixed powder to the molding agent is controlled to be 1:(0.01~0.04).
[0013] Preferably, the temperature-controlled sintering process in step 3) includes sintering the rough billet at 1150–1300°C for 1.5–3.0 h.
[0014] As a preferred option Step 3) describes a segmented sintering process for temperature-controlled sintering. The segmented sintering process includes, in sequence, low-temperature sintering at 150–200℃ for 10–20 min, medium-temperature sintering at 580–650℃ for 30–120 min, high-temperature sintering at 800–1000℃ for 1–2 h, and ultra-high-temperature sintering at 1150–1300℃ for 1.5–3.0 h; After the segmented sintering is completed, the cooling rate is controlled at ≥20℃ / min to cool the product to room temperature.
[0015] As a preferred option Step 3) describes temperature-controlled sintering performed under vacuum conditions.
[0016] A porous iron-based stainless steel material.
[0017] This invention uses porous iron-based stainless steel as the alloy substrate, primarily because it possesses excellent mechanical properties and machinability, secondly because it exhibits good corrosion resistance and low thermal expansion, making it suitable for a wide range of applications and cost-effective.
[0018] However, the oxide films commonly used in porous iron-based stainless steel, such as Cr2O3, are insufficiently protective and cannot provide long-term protection at high temperatures. Therefore, this invention further incorporates aluminum powder. The addition of Al transforms the protective film into Al2O3. However, the secondary growth of the alumina film for self-repair and protection has certain limitations. For example, under high-temperature conditions (≥1000℃), alumina film growth is relatively good, achieving rapid self-repair and protection without requiring specific oxygen partial pressure conditions. But below 1000℃, alumina mainly exists in metastable γ-Al2O3 and θ-Al2O3 states, and the transformation to stable α-Al2O3 requires a certain amount of time. Therefore, its aging properties are significantly limited, and the resulting protective performance is easily damaged by secondary processes.
[0019] To address this, the present invention further introduces oxides as oxidants to react with Al in an aluminothermic reaction, thereby achieving in-situ formation of an Al2O3 passivation film during the preparation process. The mixing of elemental powders and pre-alloyed powders solves the oxidation consumption of elemental powders during the pre-alloying process. Simultaneously, the particle size of the introduced oxide powder is much smaller than that of the pre-alloyed powder and elemental powder, effectively controlling the location and magnitude of the passivation film formation, and reducing problems such as molding difficulties caused by the large difference in thermal expansion coefficients between metals and ceramics. The coordinated composition of these three components constructs a matrix with good oxidation resistance and effectively forms a highly dense, effective, and thermally stable α-alumina film in situ on the matrix surface.
[0020] In the above process, it is also necessary to control the various main components. For example, the proportions of each component in the mixed powder can be adaptively adjusted within the above range to achieve better preparation results. The relative content of aluminum and chromium is particularly important to control. Aluminum is the reducing agent in the aluminothermic reaction and a major component in the formation of the passivation film; chromium is also crucial for improving the oxidation resistance of the alloy base. Furthermore, high-valence oxides of transition metals are usually selected for the oxide powder to promote the effective aluminothermic reduction. Common oxides such as ferric oxide, nickel oxide, and titanium oxide can all form an alumina film in situ through the aluminothermic reaction, but ferric oxide is relatively the most effective. This is because iron is the most important component of the iron-based stainless steel pre-alloy powder. When ferric oxide forms an alumina passivation film through the aluminothermic reaction, iron is also formed in situ simultaneously. Elemental iron and iron-based stainless steel pre-alloy powder have good diffusion properties. Through effective interdiffusion, the bonding stability of the in-situ alumina passivation film can be significantly improved, ensuring that the porous material has better thermal shock resistance. For nickel-based and titanium-based porous materials, the technical solution of this invention also shows that nickel oxide and titanium oxide are more effective, but nickel-based and titanium-based porous materials are more expensive and have other effective anti-corrosion and anti-oxidation methods. Therefore, the research object of this invention is mainly iron-based stainless steel materials. Furthermore, the amount and particle size of the oxides also need to be strictly controlled. As mentioned earlier, the oxide powder particle size needs to be much smaller than that of the pre-alloyed powder and aluminum powder to control the formation and thickness of the in-situ passivation film. When the particle size is too large, it is very easy to cause local enrichment and thickening, or local thinning, resulting in poor stability and protection of the in-situ passivation film. However, when the oxide powder is too fine, excessive diffusion and adhesion will occur, and even partial corrosion pits will be found under certain conditions. This may be because the excessively fine ferric oxide component will undergo short-range diffusion and react with some iron or other iron-based stainless steel pre-alloyed powder components to form intermediate or mixed valence compounds, such as ferrous oxide or magnetite, which will lead to incomplete formation of the in-situ passivation film and failure to form a complete coverage. At the same time, it will cause cracking of the substrate and a decrease in its structural strength. On the other hand, too much oxide will cause cracking after sintering, leading to material preparation failure or decreased stability. Too little oxide will result in incomplete passivation film coverage and reduced performance.
[0021] In the mixing process of step 1), the present invention can also add cemented carbide microspheres to assist in powder mixing. During the auxiliary mixing, the microsphere-to-powder ratio is controlled at (1-2):1. Simultaneously, the process is carried out under a protective atmosphere to prevent oxidation loss of the material or a certain degree of failure of the metallic aluminum powder. This process ensures that the aluminum powder, oxide powder, and main alloy pre-alloy powder are uniformly mixed before forming and reaction synthesis, thus solving the problems of metal-ceramic composite melting and forming. The mixing process allows the aluminum powder, oxide powder, and main alloy pre-alloy powder in the powder to be uniformly mixed first, ensuring that the passivation film prepared integrally can be uniformly distributed on the surface of the material skeleton.
[0022] Furthermore, the present invention also performs granulation treatment before pressing. A binder is used to granulate the powder to form relatively large particles, ensuring that the mesh size of the mixed powder is 30-100 mesh. This ensures both the uniformity of the composition and avoids the problem of poor molding effect caused by excessively large powder particle size.
[0023] In the subsequent multi-stage sintering process, a low-temperature sintering at 150–200℃ for 10–20 min is performed to remove moisture and other adsorbed gases from the sample and sintering equipment. Following this, a holding sintering at 580–650℃ for 30–120 min is performed. At this temperature, Al undergoes a diffusion reaction, and the longer sintering and holding times ensure uniform Al diffusion. Simultaneously, sintering at 800–1000℃ for 1–2 h is performed to prevent self-propagation from causing significant deformation of the material. Finally, sintering at 1150–1300℃ for 1.5–3 h ensures the material is properly formed with a good sintering neck. After sintering, rapid cooling from the high temperature is required, with a cooling rate of not less than 20℃ / min. This high cooling rate is expected to further ensure the uniform distribution of the passivation film. Furthermore, the porous alloy composition obtained through the above sintering method, combined with the low-temperature and high-temperature sintering, ensures a uniform and abundant pore structure and guarantees good mechanical properties of the alloy.
[0024] The beneficial effects of this invention are: This invention achieves the integrated preparation of iron-based stainless steel porous materials and their surface passivation films by adding aluminum and a certain amount of oxides to the alloy. The resulting in-situ passivation film composite iron-based stainless steel porous materials have broad application prospects and can be widely used in fields such as high-temperature filtration and catalyst carriers. The samples obtained from the in-situ passivation film composite iron-based stainless steel porous materials have good and uniform pore structure, excellent high-temperature corrosion resistance, convenient use process, and a longer service life. Attached Figure Description
[0025] Figure 1 The XRD pattern of the sintering evolution process of the sample prepared in Example 2 of this invention; Figure 2This is a macroscopic morphology diagram of the sintering evolution process of the sample obtained in Example 2 of the present invention; Figure 3 The above are the SEM characterization results of the sample prepared in Example 2 of this invention; Figure 4 The elemental distribution line scan results are for the sample prepared in Example 2 of this invention. Detailed Implementation
[0026] The present invention will be further described clearly and in detail below with reference to specific embodiments and the accompanying drawings. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0027] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available or obtainable by those skilled in the art; unless otherwise specified, all methods used in the embodiments of the present invention are methods mastered by those skilled in the art.
[0028] Unless otherwise specified, the iron-based stainless steel pre-alloyed powder used in the embodiments of the present invention has a mesh size of 200 mesh, the aluminum powder has a mesh size of 500 mesh, and the ferric oxide powder has a particle size of 0.1 μm.
[0029] Example 1 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloy powder, 10g aluminum powder and 12g ferric oxide powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0030] The properties of the prepared iron-based stainless steel porous material were characterized.
[0031] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0032] The pore structure parameter characterization results are shown in the table below. 38.01 13.08 1009.1
[0033] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.45% +0.89% +1.08% +1.11% +1.13% +1.14%
[0034] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 3.17 Ca (mg / L) 4.31 1.51 Ca (mg / L) 7.42 2.67
[0035] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After filtration of the same sample into mosquito coil ash solution 10 times, the Ca concentration after the tenth filtration was approximately 13.32 mg / L, indicating that the product prepared in this example has extremely high structural stability.
[0036] Example 2 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloyed powder, 10g aluminum powder and 8g ferric oxide powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0037] The properties of the prepared iron-based stainless steel porous material were characterized.
[0038] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0039] The pore structure parameter characterization results are shown in the table below.
[0040] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.41% +0.69% +0.73% +0.79% +0.81% +0.81%
[0041] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 2.19 Ca (mg / L) 4.31 1.76 Ca (mg / L) 7.42 1.41
[0042] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After filtration of the same sample into mosquito coil ash solution 10 times, the Ca concentration after the tenth filtration was approximately 13.26 mg / L, indicating that the product prepared in this example has extremely high structural stability.
[0043] In addition, XRD characterization and macroscopic photographic characterization were performed on the products obtained at each stage of the sintering process in this embodiment. See below for details. Figure 1 and Figure 2 As shown. From Figure 1 and Figure 2 The characterization results clearly show that the phase composition and structure continuously change as sintering proceeds. Further SEM characterization of the prepared iron-based stainless steel porous material sample yields the following results: Figure 3 As shown, from Figure 3 It can be seen that it has a rich porous structure. Further surface elemental distribution line scan results were obtained from the sample surface, with the results of two line scans shown below. Figure 4 As shown, from Figure 4 It can also be seen that a rich and dense aluminum oxide passivation film has formed on the surface.
[0044] Example 3 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloyed powder, 10g aluminum powder and 4g ferric oxide powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0045] The properties of the prepared iron-based stainless steel porous material were characterized.
[0046] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0047] The pore structure parameter characterization results are shown in the table below. 38.06 13.87 1037.1
[0048] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.59% +1.01% +1.12% +1.14% +1.14% +1.14%
[0049] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 6.38 Ca (mg / L) 4.31 1.65 Ca (mg / L) 7.42 1.89
[0050] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After 10 repeated filtrations of the same sample with mosquito coil ash solution, the Ca concentration after the tenth filtration was approximately 16.71 mg / L, indicating that the product prepared in this example has extremely high structural stability.
[0051] Comparative Example 1 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloy powder, 10g aluminum powder and 16g ferric oxide powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0052] The properties of the prepared iron-based stainless steel porous material were characterized.
[0053] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0054] The pore structure parameter characterization results are shown in the table below. 34.21 12.09 879.6
[0055] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.83% +1.37% +1.63% +1.68% +1.69% +1.69%
[0056] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 1.89 Ca (mg / L) 4.31 1.01 Ca (mg / L) 7.42 2.13
[0057] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After 10 repeated filtrations of the same sample with mosquito coil ash solution, the Ca concentration after the tenth filtration was approximately 14.09 mg / L.
[0058] Comparative Example 2 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloyed powder, 10g aluminum powder and 2g ferric oxide powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0059] The properties of the prepared iron-based stainless steel porous material were characterized.
[0060] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0061] The pore structure parameter characterization results are shown in the table below. 37.14 14.12 1031.5
[0062] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.85% +1.36% +1.49% +1.68% +1.79% +1.85%
[0063] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 1.87 Ca (mg / L) 4.31 2.04 Ca (mg / L) 7.42 3.79
[0064] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After filtration of the same sample into mosquito coil ash solution 10 times, the Ca concentration after the tenth filtration was approximately 39.01 mg / L.
[0065] Comparative Example 3 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g (grade) 316L iron-based stainless steel pre-alloyed powder and 10g aluminum powder evenly. Add hard corundum alloy balls during the mixing process. The ball-to-powder mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0066] The properties of the prepared iron-based stainless steel porous material were characterized.
[0067] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0068] The pore structure parameter characterization results are shown in the table below. 36.86 14.87 1095.2
[0069] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.98% +1.52% +1.71% +1.94% +1.95% +2.05%
[0070] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 2.23 Ca (mg / L) 4.31 2.71 Ca (mg / L) 7.42 4.21
[0071] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After filtration of the same sample into mosquito coil ash solution 10 times, the Ca concentration after the tenth filtration was approximately 202.83 mg / L.
[0072] The comparison between Examples 1-3 and Comparative Examples 1-3 shows that when the amount of ferric oxide added is between 0 and 12 wt%, the pore structure of the material does not change significantly. However, the pore structure parameters of Comparative Example 1 decrease significantly. This may be because excessive ferric oxide participates in the reaction, causing the passivation film in the pore structure to have a certain impact on the pore structure. The protective aging characterization results of Comparative Examples 2 and 3 show that when the iron oxide content is too low, its aging performance decreases significantly, and the oxidation weight gain increases significantly. This is because increasing the amount of oxide powder in the range of 0-12 wt% leads to enhanced aging performance. However, when the amount is too large, such as in Comparative Example 1, the stability of the passivation film weakens, leading to an increase in oxidation weight gain. This may be because too much elemental iron is reduced by the aluminothermic reduction reaction, causing it to be further oxidized during the high-temperature oxidation process, and to some extent damaging the passivation film.
[0073] The filtration accuracy and stability characterization results show that the filtration accuracy increases with the addition of ferric oxide. However, both excessive and insufficient ferric oxide will lead to a significant decrease in the stability of the passivation membrane.
[0074] Comparative Example 4 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g of 316L iron-based stainless steel pre-alloy powder, 10g of aluminum powder and 8g of ferric oxide powder (particle size 0.05μm) evenly. Add hard corundum alloy balls during the mixing process. The ball-to-material mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0075] The properties of the prepared iron-based stainless steel porous material were characterized.
[0076] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0077] The pore structure parameter characterization results are shown in the table below. 37.21 13.11 1022.67
[0078] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.48% +0.83% +1.02% +1.29% +1.43% +1.56%
[0079] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 3.02 Ca (mg / L) 4.31 1.39 Ca (mg / L) 7.42 2.39
[0080] The stability of the passivation membrane was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After filtration of the same sample into mosquito coil ash solution 10 times, the Ca concentration after the tenth filtration was approximately 18.29 mg / L.
[0081] The characterization results above show that using ultrafine ferric oxide powder retains the pore structure of the product to some extent, but significantly reduces its protective efficacy and passivation film stability. Furthermore, surface elemental scanning characterization revealed a change in the Al-O atomic ratio, an increase in Fe content with a positive correlation, and SEM characterization showed more microcracks. This indicates that excessively fine ferric oxide powder does not effectively optimize the product. Similarly, experiments were conducted with ferric oxide powders of 0.5 μm, 1.0 μm, 1.5 μm, and 2.0 μm particle sizes. The results show that using ferric oxide powder with a particle size of 0.1–1.5 μm maintains relatively good passivation film stability and protective efficacy, ensuring the effective stability of the product obtained in this invention. However, the product prepared with 1.5 μm ferric oxide powder exhibits a decrease in filtration accuracy. Therefore, the optimal ferric oxide powder particle size should be 0.1–1.0 μm.
[0082] Comparative Example 5 A porous iron-based stainless steel material, said porous material being prepared by the following method: 1) Mix 100g of 316L iron-based stainless steel pre-alloy powder, 10g of aluminum powder and 11.2g of nickel oxide powder (particle size of 0.1μm, providing an equimolar amount of oxygen) evenly. Add hard corundum alloy small balls during the mixing process. The ball-to-powder mass ratio is 2:1. Nitrogen gas is passed through the mixing process for protection. After the mixing is completed, a mixed powder is obtained. 2) Weigh 100g of the mixed powder obtained in step 1), heat 10g of ethanol to 50℃ using a water bath heating method, add 2g of stearic acid, and pour it into the mixed powder after it dissolves. Stir it into a paste, and then place it in a vacuum drying oven at 60℃ for 2 hours. After it is fully dried, take it out and sieve it through a 30-mesh sieve to obtain granulated powder. Use a molding method to mechanically shape the powder. Weigh 2.5g of powder each time and press it at a pressure of 200MPa to obtain a sheet-like preform. 3) The preform is sintered in a vacuum sintering furnace and then evacuated. It is then sintered sequentially at 150°C for 15 min, at 580°C for 60 min, at 650°C for 60 min, at 800°C for 90 min, and finally sintered at 1200°C for 2 h to obtain a porous iron-based stainless steel material.
[0083] The properties of the prepared iron-based stainless steel porous material were characterized.
[0084] Characterization includes pore structure parameter characterization, protection aging characterization, filtration accuracy characterization, and passivation membrane stability characterization.
[0085] The pore structure parameter characterization results are shown in the table below. 40.21 11.98 1053.9
[0086] The protective aging characterization involved placing the sample in an air atmosphere at 800℃ for oxidation. Samples were taken and weighed every 30 minutes, and the weight gain rate relative to the initial weight was calculated. The characterization results are shown in the table below. +0.56% +0.73% +0.89% +1.01% +1.22% +1.35%
[0087] The filtration accuracy was characterized by filtration of mosquito coil ash solution to simulate actual flue gas filtration, with Ca element selected as the reference amount. The concentrations of the original solutions after filtration were compared using different embodiments, and the characterization results are shown in the table below. Ca (mg / L) 46.39 2.39 Ca (mg / L) 4.31 1.40 Ca (mg / L) 7.42 2.38
[0088] The passivation membrane stability was characterized by multiple filtrations of mosquito coil ash solution (original concentration 46.39 mg / L), with Ca element used as a reference. After 10 repeated filtrations of the same sample with mosquito coil ash solution, the Ca concentration after the tenth filtration was approximately 15.72 mg / L.
[0089] The characterization results above show that replacing ferric oxide with nickel oxide in the reaction significantly alters the actual preparation effect, especially in terms of protection against failure. Iron oxide demonstrates a far superior effect compared to nickel oxide because the in-situ formation and diffusion bonding of elemental iron effectively improves the stability of the alumina passivation film's bond with the substrate. While stainless steel pre-alloy powder also contains nickel, it is not a primary component; therefore, although it possesses some diffusion bonding effect, it is not as strong and effective as that of iron. Particularly in the 120-150 min range, the explosive increase in weight suggests a possible loss of the passivation film and further oxidation, although the degree of detachment is small and relatively controllable.
[0090] Further experiments were conducted using an equivalent amount of titanium oxide. The results showed that although the same sample could be prepared using titanium oxide, its performance in preventing failure and the stability of the passivation film were inferior to those of the sample prepared with nickel oxide. Therefore, it is evident that ferric oxide is inexpensive, readily available, and provides the best preparation results, making it virtually irreplaceable.
Claims
1. A method for preparing an iron-based stainless steel porous material, characterized in that, The method includes: 1) Take iron-based stainless steel pre-alloy powder, aluminum powder and oxide powder and mix them evenly to obtain a mixed powder; 2) Press the mixed powder obtained in step 1) into a rough blank; 3) The rough blank obtained in step 2) is subjected to temperature-controlled sintering to obtain iron-based stainless steel porous material; Step 1) The oxide powder is ferric oxide powder; Step 1) The amount of oxide powder used is 8-12 wt% of the mass of the iron-based stainless steel pre-alloyed powder; Step 1) The oxide powder has a particle size of 0.1–1.0 μm; Step 1) The amount of aluminum powder used is 5-10 wt% of the mass of the iron-based stainless steel pre-alloyed powder. Step 1) The iron-based stainless steel pre-alloyed powder and aluminum powder have a mesh size of 200-500 mesh; Step 3) describes a segmented sintering process for temperature-controlled sintering. The segmented sintering process includes, in sequence, low-temperature sintering at 150–200 °C for 10–20 min, medium-temperature sintering at 580–650 °C for 30–120 min, high-temperature sintering at 800–1000 °C for 1–2 h, and ultra-high-temperature sintering at 1150–1300 °C for 1.5–3.0 h; After the segmented sintering is completed, the cooling rate is controlled at ≥20 ℃ / min to cool the product to room temperature.
2. The method for preparing a porous iron-based stainless steel material according to claim 1, characterized in that, Step 1) The stainless steel pre-alloyed powder contains 10-20 wt% Cr, 5-10 wt% Ni, and the balance is Fe and unavoidable impurities.
3. The method for preparing a porous iron-based stainless steel material according to claim 2, characterized in that, Step 2) Granulation treatment is performed on the mixed powder before pressing it into a rough blank; The granulation process involves mixing and stirring the mixed powder and molding agent until a paste is formed, drying and sieving under a protective atmosphere or vacuum to obtain a mixed powder with a mesh size of 30 to 100.
4. The method for preparing a porous iron-based stainless steel material according to claim 3, characterized in that, The molding agent is dissolved in a solvent and then mixed with the mixed powder. The mass ratio of the molding agent to the solvent is (0.05~0.20):1, and the solvent is ethanol and / or water. When the mixed powder is mixed with the molding agent, the mass ratio of the mixed powder to the molding agent is controlled to be 1:(0.01~0.04).
5. The method for preparing a porous iron-based stainless steel material according to claim 1, characterized in that, Step 3) The temperature-controlled sintering is carried out under vacuum conditions.
6. A porous iron-based stainless steel material prepared by any one of claims 1 to 5.
Citation Information
Patent Citations
Method for preparing ceramic reinforced metal-based porous composite material
CN101168805A
Iron-based porous material with resistance to high temperature oxidation and alkali corrosion and preparation method thereof
CN107267847A